FORMATION OF THE NEED FOR SELF-DEVELOPMENT OF PEDAGOGICAL WORKERS BY MEANS OF FACILITATION - Олексенко, Светлана; Хоменко, Елена (SWorldJournal, 2020)
The article presents the results of a study on the level of realization of teachers 'needs in development and self-development, assessment of teachers' readiness to know themselves and readiness to self-improvement. The tasks of pedagogical facilitation